2019
DOI: 10.18043/ncm.80.4.204
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Drone-assisted Emergency Response to Cardiac Arrest

Abstract: BACKGROUND Despite evidence linking rapid defibrillation to out-of-hospital cardiac arrest (OHCA) survival, bystander use of automatic external defibrillators (AEDs) remains low, due in part to AED placement and accessibility. AED-equipped drones may improve time-to-defibrillation, yet the benefits and costs are unknown. METHODS We designed drone deployment networks for the state of North Carolina using mathematical optimization models to select drone stations from existing infrastructure by specifying the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 27 publications
0
52
0
2
Order By: Relevance
“…Bogle et al looked at the health economics aspect by cost-effectiveness perspective approach and demonstrated QALYs and ICERs with UAV technology for AED delivery. The authors employed a sensitivity analysis with a variety of assumptions, such as number of docking stations, willingness to apply AED to OHCA, survival rate, and so on, and it was still demonstrated that an AED drone network remained cost-effective over a wide range of assumptions (Bogle et al, 2019). This kind of sensitivity analysis around the cost-effectiveness of this new technology should be performed with different assumptions, especially in the other regions and countries to show the cost-effectiveness in the other situations as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bogle et al looked at the health economics aspect by cost-effectiveness perspective approach and demonstrated QALYs and ICERs with UAV technology for AED delivery. The authors employed a sensitivity analysis with a variety of assumptions, such as number of docking stations, willingness to apply AED to OHCA, survival rate, and so on, and it was still demonstrated that an AED drone network remained cost-effective over a wide range of assumptions (Bogle et al, 2019). This kind of sensitivity analysis around the cost-effectiveness of this new technology should be performed with different assumptions, especially in the other regions and countries to show the cost-effectiveness in the other situations as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 500-drone network decreased the median time of defibrillator arrival from 7.7 to 2.7 minutes. Expected survival rates doubled (24.5% versus 12.3%), resulting in an additional 30,267 Quality-adjusted life years (QALYs) (Bogle, Rosamond, Snyder, & Zègre-Hemsey, 2019).…”
Section: Estimated Reductions In Time To Defibrillation In Ohcas By Smentioning
confidence: 99%
“…With the lifespan of a drone being four years and each drone costing £15,000, the total cost to implement the drone network including 20% of the purchase price for annual maintenance, is approximately £2.11million [12], [34]. In a cost-effective analysis of utilizing AED drones in North Carolina, US, Bogle et al [34] concluded that in a large scale network, AED drones have the potential to improve OHCA survival rate while being cost-effective. However, due to the wide range of assumptions taken in that study, it is important to undertake a detailed cost-effective analysis for AED drone networks considering personnel training and maintenance.…”
Section: B Cost Of the Drone Networkmentioning
confidence: 99%
“…A study published by Bogle et al described drone-based AED deployment networks. The authors revealed that all analysed drone networks improved AED delivery time and suggested that they can improve out-of-hospital cardiac arrest survival outcomes [11].…”
Section: World Applications Of Drones In Rescue Operationsmentioning
confidence: 99%